Use of a Food Frequency Questionnaire for the Estimation of Gut Microbiota Composition Based on Dietary Patterns and Its Association with Irritable Bowel Syndrome Symptoms in the Lebanese Adult Population: A Cross-Sectional Study - Christie J. Bou Chacra; Sofi G. Julien (Advances in Public Health)
Gut microbiome analysis is costly and poses a significant challenge for determining the gut microbiota composition to facilitate the adoption of personalized nutritional interventions. Emerging evidence suggests dysbiosis as a contributor to irritable bowel syndrome (IBS), but the results remain uncertain. Moreover, IBS prevalence is becoming a public health problem in the adult Lebanese population. This study aimed at estimating the gut microbiota’s composition using a Food Frequency Questionnaire (FFQ) and exploring its correlation with IBS among Lebanese adults. A cross-sectional study was conducted for 388 adults during the summer 2023. An online questionnaire collected information about sociodemographic characteristics, anthropometric measures, health status, and dietary habits through a semiquantitative FFQ. We observed the influence of Western diet among the three patterns that were identified. Participants were clustered into two groups based on their estimated (poor or good) microbiota composition, EPMC and EGMC, respectively. We observed a significant inverse relationship between IBS symptoms and EGMC. Participants experiencing IBS symptoms were less likely to exhibit a good gut microbiota compared to those without any IBS symptoms (AOR = 0.614, 95% CI (0.402–0.937), P=0.024), and a higher adherence to the Mediterranean diet was significantly associated with lower odds of having IBS symptoms (AOR = 0.786, 95% CI (0.635–0.973), P=0.027). Our study revealed a dietary shift toward a more Westernized pattern among Lebanese adults who experienced symptoms of IBS. FFQ may be used to estimate the gut microbiota to provide customized nutritional therapy for patients suffering from IBS.